BALANCING TECHNOCRACY AND POLITICS IN THE INDONESIA’S MULTI-PARTY PRESIDENTIAL SYSTEM: LEGAL CHALLENGES IN DESIGNING STATE MINISTRIES - Mustafa Lutfi; Aditya Prastian Supriyadi; Kurniasih Bahagiati (Faculty of Law, Universitas Diponegoro, 2026)
The institutional design of state ministries is a central element of Indonesia’s constitutional system because it determines how executive authority is organised, coordinated, and made accountable. Although Article 17 of the 1945 Constitution grants the President authority to establish ministries, political practice shows that cabinet formation is shaped not only by technocratic considerations but also by coalition bargaining within Indonesia’s multiparty presidential system. This study analyses the legal politics of ministerial design, focusing on the tension between constructing a proportional and efficient cabinet and accommodating the political demands of coalition parties. Using doctrinal legal research, this study examines the formation of the Kabinet Merah Putih under President Prabowo Subianto, which consists of 48 ministries, as its main empirical reference. The analysis is conducted through normative mapping of Presidential Regulation Number 139 of 2024 and Law Number 61 of 2024, as well as functional mapping of overlapping ministerial mandates. The findings show that ministerial design in Indonesia is frequently influenced by political pragmatism, producing institutional expansion that may weaken coordination, accountability, fiscal rationality, and functional clarity. This study evaluates ministerial design through five normative criteria: effectiveness, functional proportionality, accountability, conflict-of-interest prevention, and fiscal rationality. The analysis argues that the decisive constitutional issue is not whether ministers come from partisan or non-partisan backgrounds, but whether they possess substantive competence, integrity, and accountability in performing public functions. This study also examines the relevance and limitations of a technocratic cabinet model in Indonesia by comparing practices in Singapore, Germany, Chile, and Uruguay. It argues that Indonesia requires a hybrid cabinet model that combines political representation with technocratic professionalism. Strengthening the legal framework on state ministries is therefore necessary to create a more rational, effective, accountable, and professional cabinet structure aligned with Indonesia’s constitutional objectives while preserving democratic legitimacy and executive coherence in institutional practice.